Architectural Fictions - Amy Herzog (Semiotic Review, 2013)
I first encountered the images in my neighborhood in North Brooklyn, on billboards posted next to construction sites or in the windows of pop-up realty storefronts. This imagery is ubiquitous in “up-and-coming” urban neighborhoods. Empty lots are digitally metamorphosed into gleaming glass condos and retail arcades. These virtual constructs are often populated by uncanny figures, pixelated people engaged in a range of activities (talking on cell phones, carting small children or armloads of shopping bags). The pictured environments are eerily sterile, presenting a stark model of the future “developed” city, and of its inhabitants.   I’ve found myself haunted by these visualizations, in particular by their deployment of these tiny “cut out people.” What follows is my attempt to think through the embodied implications of this disembodied aesthetic, one that has connections to digital cinema and video game technology, but that extends this imagery into often under-theorized realms.